1988
DOI: 10.1111/j.1476-5381.1988.tb11471.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of some muscarinic agonists on evoked surface‐negative field potentials recorded from the guinea‐pig olfactory cortex slice

Abstract: 1 The effects of muscarinic receptor agonists on the electrically-evoked surface-negative field potential (N-wave) were measured in the guinea-pig olfactory cortex slice maintained in vitro.2 Bath-superfusion of (±)-muscarine, acetylcholine (ACh), carbachol (CCh), or methacholine (MCh) (10-200pM) produced reversible, dose-dependent depressions of the N-wave (ACh and MCh effects were observed in the presence of 1OyM neostigmine). The order of potencies (based on agonist dose causing 50% field depression: IC5o) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Acetylcholine causes similar physiological effects in most cortical structures, including direct depolarization of neurons Benardo & Prince, 1982;Madison & Nicoll, 1984) and enhancement of long-term potentiation (Blitzer, Gil, & Landau, 1990;Brocher, Artola, & Singer, 1992;Patil, Linster, Lubenov, & Hasselmo, 1998). Experimental data in a number of different regions also shows that acetylcholine strongly suppresses excitatory glutamatergic synaptic transmission via presynaptic inhibition at intrinsic, recurrent synapses in cortical structures (Dutar & Nicoll, 1988;Gil, Connors, & Amitai, 1997;Hasselmo, Schnell, & Barkai, 1995;Hounsgaard, 1978;Hsieh, Cruikshank, & Metherate, 2000;Linster, Wyble, & Hasselmo, 1999;Williams & Constanti, 1988). In contrast, acetylcholine usually causes less presynaptic inhibition at afferent fiber synapses (Gil et al, 1997;Hsieh et al, 2000;Linster et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Acetylcholine causes similar physiological effects in most cortical structures, including direct depolarization of neurons Benardo & Prince, 1982;Madison & Nicoll, 1984) and enhancement of long-term potentiation (Blitzer, Gil, & Landau, 1990;Brocher, Artola, & Singer, 1992;Patil, Linster, Lubenov, & Hasselmo, 1998). Experimental data in a number of different regions also shows that acetylcholine strongly suppresses excitatory glutamatergic synaptic transmission via presynaptic inhibition at intrinsic, recurrent synapses in cortical structures (Dutar & Nicoll, 1988;Gil, Connors, & Amitai, 1997;Hasselmo, Schnell, & Barkai, 1995;Hounsgaard, 1978;Hsieh, Cruikshank, & Metherate, 2000;Linster, Wyble, & Hasselmo, 1999;Williams & Constanti, 1988). In contrast, acetylcholine usually causes less presynaptic inhibition at afferent fiber synapses (Gil et al, 1997;Hsieh et al, 2000;Linster et al, 1999).…”
Section: Introductionmentioning
confidence: 94%
“…The methods used for preparation and recording from guinea-pig olfactory cortex slices are described in detail in the accompanying paper (Williams & Constanti, 1988). Schild plots (Arunlakshana & potential records show the peak N-wave depression measured after a 2 min bath-application of CCh, and on the far right is the corresponding slow-speed chart record of peak N-wave amplitude (individual downward deflections cannot be distinguished).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we have investigated quantitatively the actions of pirenzepine on this preparation, in an attempt to determine the receptor subtype responsible for generating this muscarinic response. We have also attempted to clarify the actions of oxotremorine, which appeared to antagonize the muscarinic responses (Williams & Constanti, 1988). Some of the data in this study have been reported in a preliminary form Williams & Constanti, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations